English as Business Lingua Franca: Examining the Use of English in Indonesian Online Business - Sri Wahyuningsih; Firda Ziyana Untsa (Universitas Lancang Kuning, 2023)
English has become a global language due to its widespread usage around the world, which has also influenced the business world. The term